Storytelling como herramienta de comunicación digital para fortalecer la relación entre el Gobierno Autónomo Descentralizado del cantón San Miguel y la ciudadanía, período enero- junio 2025. - Chacha Toapanta, Fanny Maricela (2025)
This study investigates the implementation of storytelling as a digital communication tool to improve the relationship between the Decentralized Autonomous Government of the Canton of San Miguel and its citizens during the first half of 2025. It is based on the observation that, despite the existence of official digital platforms, communication remains largely informative and one-way, which restricts closeness, trust, and citizen participation. Storytelling is presented as a novel strategy for transforming institutional messages into relevant narratives capable of generating empathy, identity, and recall. By sharing stories that showcase daily life, community values, and local government initiatives, the study seeks to humanize public administration and foster a deeper connection with the population. It is concluded that a systematic implementation of storytelling in the GAD's digital communication could improve the institutional image, increase citizen participation, and establish a more open and collaborative relationship with the community.